Combined Forced and Free Convection in the Entrance Region of a Horizontal Pipe - Montesclaros, Morrison Sistuzon (Philippine Engineering Journal; Vol 3 No 2 (1982), 2021)
The effect of buoyancy on laminar forced convection in the entrance region of a uniformly heated horizontal pipe, where the velocity and temperature fields are developing simultaneously, is investigated for the case of Gr = 5000. All of the terms of the time-dependent governing equations are taken into account so that the results obtained can be applied to low Prandtl number fluids for which the results obtained from large Prandtl number assumptions are no longer valid. A novel iterative method is developed to solve nonlinear partial differential equations, and has proven to ensure stability and faster rate of convergence. The developing primary and secondary velocity profiles, developing temperature field, and local and average Nusselt numbers are presented to clarify the free convection effect. Values are compared with those obtained from pure forced convection.